Fractures of the Foot and Ankle A Clinical Casebook (Springer International Publishing, 2018)
Comprised exclusively of nearly two dozen clinical cases covering common fractures of the foot and ankle, this concise, practical casebook will provide orthopedic and foot and ankle surgeons with the best real-world strategies to properly manage both open and closed fractures of the ankle, calcaneus, talus and metatarsals. Each chapter is a case that opens with a unique clinical presentation, followed by a description of the diagnosis, assessment and management techniques used to treat it, as well as the case outcome and clinical pearls. Cases included illustrate the surgical management of unimalleolar, bimalleolar and trimalleolar fractures of the ankle, injuries to the talus and calcaneus, midfoot and metatarsals, in addition to malunions and nonunions, Lisfranc injuries, and the Charcot foot and ankle. Pragmatic and reader-friendly, Fractures of the Foot and Ankle: A Clinical Casebook will be an excellent resource for orthopedic su rgeons, foot and ankle specialists and podiatrists confronted with these common injuries to the lower extremity.